Whereto with institutions and governance challenges in African wildlife conservation? - Edwin Muchapondwa; Jesper Stage (Environmental Research Letters, 2015)
African wildlife conservation has been transformed, shifting from a traditional, state-managed government approach to a broader governance approach with a wide range of actors designing and implementing wildlife policy. The most widely popularized approach has been that of community-managed nature conservancies. The knowledge of how institutions function in relation to humans and their use of the environment is critical to the design and implementation of effective conservation. This paper seeks to review the institutional and governance challenges faced in wildlife conservation in southern and eastern Africa. We discuss two different sets of challenges related to the shift in conservation practices: the practical implementation of wildlife governance, and the capacity of current governance structures to capture and distribute economic benefits from wildlife. To some extent, the issues raised by the new policies must be resolved through theoretical and empirical research addressed at wildlife conservation per se. However, many of these issues apply more broadly to a wide range of policy arenas and countries where similar policy shifts have taken place.